Effect of phenolics on Drechsleva oryzae - N. ELANGOVAN, P.T. KALAICHELVAN and (Indian Phytopathology, 2002)
Both resorcinol and phloroglucinol inhibited growth of D. oryzae [Cochliobolus miyabeanus] at 10 mM. The mode of action of these phenols was studied on hexokinase, malate dehydrogenase, succinate dehydrogenase and fumarase of C. miyabeanus.